Crime and Behaviour : An Introduction to Criminal and Forensic Psychology - Khader, Majeed, 1966- (World Scientific, 2019)
Crime and Behaviour: An Introduction to Criminal and Forensic Psychology is the first textbook to provide a detailed overview of criminal psychology in Singapore. The textbook puts together ideas relating to crime, crime prevention, and criminal psychology, as it occurs in the Singaporean context. While leveraging on psychology as an anchor, the book adopts a multidisciplinary perspective and examines the forensic sciences angle, legal issues, and the investigative perspectives of crimes.The chapters cover criminal justice agencies in Singapore, theories of crime, deception and lying behaviors, sex crimes, violent crimes, crime prevention, terrorism, and psychology applied in legal settings. Each chapter contains case studies of actual cases and ends with questions for discussion and research, making this a valuable text for courses in university and in law enforcement settings.